Food shortages and farm prices - Hugh Corbet (Intereconomics, 1974)
In the forthcoming GATT negotiations attention is expected to focus more than in any previous round on the problems in international agricultural trade. The author suggests a set of courses that might be able to restore some semblance of order in world agricultural markets.
Keywords: 330; GATT